Refractive error, axial length and anterior chamber depth of the eye in British adults: the EPIC-Norfolk Eye Study. Issue 7 (1st July 2010) - Foster, P J; Broadway, D C; Hayat, S; Luben, R; Dalzell, N; Bingham, S; Wareham, N J; Khaw, K-T
Abstract : Purpose: To describe the distribution, and demographic and socioeconomic correlates of refractive error and related ocular biometry in an older British population. Methods: Refractive error was measured using an auto-refractor without cycloplegia. Pseudophakic individuals and those who had undergone refractive surgery were excluded from analysis. Axial length and anterior chamber depth were measured using partial coherence laser interferometry. Occupation category and highest educational achievement were recorded. Results: Biometric data were available for 2519 people (1090 men, 1429 women; 93.2% of all participants) aged 48 to 88 years. Refractive data were available for both eyes in 2210 bilaterally phakic participants. Among phakic individuals, axial length of the eye was strongly inversely correlated with refractive error in both men and women (p<0.001). Axial length of the eye was strongly, independently related to height, weight and social class, but most strongly related to educational achievement. In contrast, anterior chamber depth varied with age and sex, but not with socioeconomic status. There was a significant inverse association between anterior chamber depth and refraction in women (p<0.001) but not in men (p=0.495). Conclusion: Refractive error in this predominantly white older UK population was associated with axial biometry and sociodemographic characteristics. Educational status was the strongest determinant of axial length.